AATF is Overexpressed in Human Head and Neck Squamous Cell Carcinoma and Regulates STAT3/Survivin Signaling - Fu L (Dove Medical Press, 2021)
Lin Fu,1,2 Quanxiu Jin,3 Qianze Dong,1,2 Qingchang Li1,2 1Department of Pathology, College of Basic Medical Science, China Medical University, Shenyang, People’s Republic of China; 2Department of Pathology, The First Affiliated Hospital of China Medical University, Shenyang, People’s Republic of China; 3Department of Breast Surgery, Cancer Hospital of China Medical University, Liaoning Cancer Hospital and Institute, Shenyang, People’s Republic of ChinaCorrespondence: Qingchang LiDepartment of Pathology, College of Basic Medical Science, China Medical University, Shenyang, People’s Republic of ChinaEmail qcli@cmu.edu.cnObjective: Dysregulation of apoptosis antagonizing transcription factor (AATF) has been implicated in several cancers. However, its involvement in human head and neck squamous cell carcinoma (HNSCC) remains unclear. This study aimed to explore the expression pattern and biological roles of AATF in head and neck squamous cell carcinoma tissues and cell lines.Methods: Immunohistochemistry was used to detect the level of AATF protein in 119 cases of HNSCC samples. CCK-8, colony formation, Annexin V/PI staining, Western blotting and RNA-sequencing were carried out to examine the change of proliferation, apoptosis and potential underlying mechanisms.Results: Immunohistochemical staining showed that AATF was elevated in HNSCC, and high AATF level correlated with higher stage. The Cancer Genome Atlas (TCGA) and Oncomine data showed upregulated AATF expression in HNSCC compared with normal tissues. TCGA data also suggested that high AATF expression correlated with poor patient survival. Ectopic AATF expression upregulated the cell growth and colony formation ability in both FaDu and Detroit 562 cell lines, while AATF siRNA decreased the cell proliferation rate and colony numbers. AATF overexpression also decreased cisplatin sensitivity, downregulated cisplatin-induced apoptosis. Mechanistically, AATF overexpression upregulated survivin, while AATF knockdown downregulated survivin. RNA-sequencing (RNA-seq) and Gene Set Enrichment Analysis (GSEA) suggested that AATF knockdown decreased STAT3 signaling. Western blotting showed that AATF overexpression upregulated while AATF knockdown downregulated STAT3 phosphorylation. There was a positive correlation between AATF and survivin mRNA based on TCGA data analysis. Blockage of STAT3 signaling using inhibitor downregulated survivin expression and largely abolished the effects of AATF on survivin.Conclusion: Our results showed that AATF was overexpressed in human HNSCC. AATF promoted cisplatin resistance and reduced apoptosis possibly through regulation of STAT3/survivin signaling. AATF could serve as a potential therapeutic target in HNSCC.Keywords: AATF, survivin, STAT3, head and neck squamous cell carcinoma